Implementación del recurso educativo digital Aprendamos Escritura, como apoyo al proceso de enseñanza-aprendizaje en la asignatura de Lengua y Literatura del décimo grado de educación general básica paralelo “A” del Colegio de Bachillerato Beatriz Cueva de Ayora, en el año lectivo 2022-2023. - Gutierres Camacho, Luis Miguel (2023)
Education has undergone an important change thanks to the incorporation of digital educational resources, which has revolutionized the teaching-learning process and provided new opportunities for access and knowledge assimilations; currently, we witnessed a constant evolution in the classroom, where technological resources perform a fundamental role to improve the educational experience, for this reason, the present research was based on the description of the digital educational resource Aprendamos Escritura (Let's Learn Writing) from the technical, methodological and pedagogical structure. In addition, it was integrated into the micro-curricular planning of the writing block of unit 2 in the tenth-grade Language and Literature subject, then the micro-curricular proposal was implemented with the inclusion of the resource in the classroom. The research took place at the Beatriz Cueva de Ayora High School, employing a methodology that combines the deductive-inductive method, quantitative approach, cross-sectional research design and exploratory-descriptive scope; the population corresponded to a teacher and 38 students. It should be noted that as the main results after the technical, methodological and pedagogical description of the digital educational resource, it was integrated into the micro-curricular planning of the writing block of unit 2 in the subject of Language and Literature, six plans were adapted, incorporating strategies and activities under the TPACK methodology, dividing them into didactic moments for its implementation, six classes were observed; in contrast to the research, they were supported by the opinion of the teacher and students on the use and management of the digital educational resource, as a result, it was evidenced that the digital educational resource Aprendamos Escritura contributes positively to the teaching-learning process of students. Keywords: Digital Educational Resource, Micro-curricular planning, Classroom observation, Didactic moments, ICT.